Finance-driven sustainable development: the impact of green finance on agricultural non-point source pollution and its pathways - Shen, Yang; Zhang, Xiuwu (Frontiers in Sustainable Food Systems, 2024)
IntroductionPollutants from farming and rural life have a serious negative impact on water and soil. The advantages of green finance in financial support and credit management can guide the green transformation of agricultural production, thus protecting the ecological environment.MethodsBased on panel data from 30 provinces in China from 2005 to 2021, the study used inventory analysis, entropy method and two-way fixed effect model to analyze the impact of green finance on agricultural non-point source pollution (ANSP) and the mediating mechanism.ResultsANSP has experienced an inverted U-shaped trend of first rising and then falling, and the rural ecological environment is improving. At the time level, the ANSP produced by agricultural production in China experienced an inverted U-shaped evolution trend of first increasing and then decreasing during the sample period. At the spatial level, ANSP has a significant low regional differentiation. The ANSP of the central region and the coastal economic development area is higher than that of the western region. The results of linear regression show that green finance has a negative effect on ANSP. Promoting green finance in rural areas can effectively guide the green transformation of agriculture and reduce the dependence of crop cultivation on fertilizers and pesticides. This result held even after the elimination of endogeneity and after various tests. Land transfer and environmental supervision are important intermediary mechanisms. Under the influence of these two economic variables, the role of green finance in pollution reduction can be fully brought into play. However, there is regional heterogeneity in the negative effects of green finance on ANSPs. Its effect on pollution reduction is stronger in major grain-producing areas and regions with well-developed digital financial infrastructure.DiscussionThis study confirms once again that green finance has a negative effect on ANSP, and the findings help to decouple the development of the agricultural economy from emissions. The outstanding contribution of this study is the discovery of the role of land transfer and government environmental regulation. I order to give full play to the role of green finance in pollution reduction, this study provides relevant policy measures. These measures are intended to improve the green finance system and business model in agriculture and rural areas.